Configurational mechanics of materials / edited by Reinhold Kienzler, Gerard A. Maugin - Kienzler, Reinhold; Maugin, Gerald A. (CISM courses and lectures, 2001)
These lecture notes cover numerous elements of configurational mechanics, including mathematical foundations, linear and nonlinear elasticity and continuum mechanics, coupled fields, fracture mechanics, as well as strength of materials.